2010
DOI: 10.1111/j.1755-148x.2010.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell vaccination in human melanoma: relationships between clinical effects and vaccine parameters

Abstract: SummaryEleven years have passed since the start of the first trial of dendritic cell (DC) vaccination for melanoma.A review of 54 trials was performed to evaluate the relationship between clinical effects and vaccine para-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 83 publications
(318 reference statements)
1
38
0
Order By: Relevance
“…However, the killing induced by alt-2 DC either via CD8 The mechanisms responsible for this dichotomy between an Agspecific and an innate mediated tumor killing might be due to the following: 1) Competition of effector cells for target during the assay. Despite the 1:1 ratio used in the degranulation assay, it is possible that in donors with higher levels of HLA and/or KIR mismatching with the used target cells, the enhanced innate killing might lead to the lack of targets for the adaptive response (2). The different outcome might be also mediated by distinct processes during the DC priming.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the killing induced by alt-2 DC either via CD8 The mechanisms responsible for this dichotomy between an Agspecific and an innate mediated tumor killing might be due to the following: 1) Competition of effector cells for target during the assay. Despite the 1:1 ratio used in the degranulation assay, it is possible that in donors with higher levels of HLA and/or KIR mismatching with the used target cells, the enhanced innate killing might lead to the lack of targets for the adaptive response (2). The different outcome might be also mediated by distinct processes during the DC priming.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical trials in different tumor entities have revealed safety and tolerability of such treatment. However, despite a frequent vaccineinduced expansion of precursor cells in the blood and/or the induction of delayed-type hypersensitivity, the rate of objective clinical responses obtained in tumor patients is very limited (1,2). For this reason, an optimization of the protocol for vaccine DC production as well as their deep functional characterization is urgently needed to improve their clinical implementation.…”
mentioning
confidence: 99%
“…and matured ones (8,9). Importantly, a plethora of clinical trials have demonstrated that DC vaccines are safe and well tolerated by cancer patients (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Currently DC vaccination is widely applied world wide with clinical responses achieved in up to 54% of patients (4,5). Therefore DC immu notherapy should be individualized in order to select cancer patients who would most likely respond to this kind of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major disadvantages of this therapeutic strategy appears to be an induction of immunotolerance (in the context of the tumor microenvironment) and of immu nosuppressive T reg cells (Beyer and Schultze, 2009). To date, DC treatment protocols have been seen to be ineffective against advanced melanoma (Nakai et al, 2010).…”
Section: Immune Cells Modulation and Immunotherapy In Melanomamentioning
confidence: 99%